2012
DOI: 10.2478/v10086-012-0001-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different diets on body mineral content, growth, and survival of barbel, Barbus barbus (L.), larvae under controlled conditions

Abstract: Abstract. The experiment tested three formulated dry diets at 25°C to determine their effects on larval Barbus barbus (L.) body mineral composition, growth, and survival. Live Artemia nauplii were fed to all the larvae for the first 5 days of the experiment. From day 6 to day 25 inclusive, nauplii were the reference diet in one group, whereas the three other groups were fed dry diets exclusively. On D1 the fish body comprised 6.71% ash, 1.20% P, 0.35% Ca, and 0.09% Mg (dry matter), but initial feeding with nau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 26 publications
0
5
0
4
Order By: Relevance
“…Phosphorus is the most important mineral because it is not available in the aquatic environment and can only be obtained from feed. Phosphorus deficiency will cause decreased skeletal development and bone deformation [30,31]. Microminerals are needed only in small amounts but have a very important role.…”
Section: Palm Oil In Fisheriesmentioning
confidence: 99%
“…Phosphorus is the most important mineral because it is not available in the aquatic environment and can only be obtained from feed. Phosphorus deficiency will cause decreased skeletal development and bone deformation [30,31]. Microminerals are needed only in small amounts but have a very important role.…”
Section: Palm Oil In Fisheriesmentioning
confidence: 99%
“…Phosphorus deficiency in the fish bodies can lead to excessive fat accumulation and poor skeletal mineralization and deformity [3]. It has also been shown that some phosphorus-containing compounds, such as phosphatidylinositol, play a very important role in preventing skeletal deformities [57]. Because the content of this mineral in the water is too low, and moreover, the efficiency of its absorption from feed is low, P should be supplemented with the feed [58].…”
Section: Phosphorus Concentrationmentioning
confidence: 99%
“…En los establecimientos piscícolas, un gran número de peces puede presentar alteraciones en el normal desarrollo esquelético durante el período larval manifestando diferentes tipos de malformaciones , a menudo asociadas a los sistemas de cría intensivos o tipo de alimentación (Boglione et al, 2001;Villeneuve et al, 2005;Sfakianakis et al, 2006;Sikorska et al, 2012).…”
Section: Introductionunclassified
“…De todos estos factores, los nutricionales juegan un rol esencial en la aparición de alteraciones esqueléticas durante los primeros estadios de vida (Cahu et al, 2003), viéndose incrementada su incidencia con el uso de microdietas (Kanazawa, 1981;Villeneuve et al, 2005;Sikorska et al, 2012).…”
Section: Introductionunclassified